The Use of Behaviourism Approach in Writing a Narrative Text Applied to Grade Class XI of SMK Negeri 1 Pancur Batu-Deli Serdang, Sumatera Utara Academic Year 2016/2017 - Arifulhak Aceh (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
There were some reasons why indirect feedback can be durable, but it would kept only in mind of receiver and the feedback can just lost in certain time. In contrast, the indirect feedback, the thought and comment would be saved for every long time in memories. The data of this research consisted of two kinds. They were quantitative data (Writing Narrative text result) and the qualitative data (diary notes and observation sheet) which had been gathered within two cycles. Cycle I consisted of three meetings and cycle II consisted of two meetings and there was writing narrative test I in the first meeting to get the students’ basic level understanding that was pre test. So, totally there were six tests in five meetings in this research. From this research, there was an increased improvement in writing narrative text by using behaviourism approach, because this theory displays more attention from the teacher to the students.